Penerapan Sanksi Terhadap Pemilik Warung Remang-Remang Berdasarkan Peraturan Daerah Kabupaten Kuantan Singingi Nomor 14 Tahun 2010 Tentang Perubahan Atas Peraturan Daerah Kabupaten Kuantan Singingi Nomor 20 Tahun 2002 Tentang Penyakit Masyarakat Oleh Pemerintah Kabupaten Kuantan Singingi - Erianda, Septi Audia; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Disease Society is the behavior of community members who are not in accordance with the values and social norms that can cause unrest and unrest in society. Dimly lit stalls is one of societys ills are prevalent among the public, such as in Kuantan Singingi. Dimly lit stalls are stalls were deserted place that has dim lighting, is open at night and usually sell liquor, drugs, and sex. Penalties are given to the owner of dimly lit stalls that provide infrastructure disease in a community governed Singingi Kuantan District Regulation No. 14 Year 2010 on Amendment Singingi Kuantan District Regulation No. 20 Year 2002 on Disease Society.This research included sociological research, in this case the researchers immediately conduct investigation in complete and clear about the issues examined. The study was conducted by means of interviews with law enforcement officials Kuantan Singingi and conducted interviews to shopkeepers dim. In conducting this study, researchers wanted to see how the application of sanctions against the shop owner dimly lit by District Regulation Kuantan Singingi No. 14 Year 2010 on the Amendment of Regional Regulation No. 20 of 2002 on Diseases Society of Government Kuantan Singingi, whether the factors inhibiting the implementation of sanctions against shop owner dimly lit by District Regulation Kuantan Singingi No. 14 Year 2010 on Amendment District Regulation Kuantan Singingi No. 20 Year 2002 on Diseases Society by Government Kuantan Singingi and how the Governments efforts in addressing the dimly lit stalls in the Regency Kuantan Singingi.The results of this study are, first, that the imposition of sanctions against the owners dimly lit stalls are not based on existing regulations, both are factors inhibiting the implementation of sanctions, namely a lack of funds, lack of human resources owned and the lack of legal institutions, and the third is the governments attempt to handle dimly lit stalls in the district of Kuantan Singingi are conducting raids and patrols, socializing, give a reprimand or a warning and make a statement.Keywords: Implementation â Sanctions - Disease Society